Vascular endothelial growth factor (VEGF) and VEGF-receptor expression in placenta of hyperglycemic pregnant women - Pietro, L.; Daher, S.; Rudge, Marilza Vieira Cunha [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Damasceno, Débora Cristina [UNESP]; Sinzato, Y. K. [UNESP]; Bandeira, C.; Bevilacqua, E. (W B Saunders Co Ltd, 2010)
Hyperglycemia occurs in a variety of conditions such as overt diabetes, gestational diabetes and mild hyperglycemia, all of which are generally defined based on the oral glucose tolerance test and glucose profiles. Whereas diabetes has received considerable attention in recent decades, few studies have examined the mechanisms of mild hyperglycemia and its associated disturbances. Mild gestational hyperglycemia is associated with macrosomia and a high risk of perinatal mortality. Morphologically, the placenta of these women is characterized by an increase in the number of terminal villi and capillaries, presumably as part of a compensatory mechanism to maintain homeostasis at the maternal-fetal interface. In this study, we analised the expression of VEGF and its receptors VEGFR-1 (Flt-1) and VEGFR-2 (KDR) in placentas from mildly hyperglycemic women. This expression was compared with that of normoglycemic women and women with gestational and overt diabetes. Immunohistochemistry revealed strong staining for VEGF and VEGFR-2 in vascular and trophoblastic cells of mildly hyperglycemic women, whereas the staining for VEGFR-1 was discrete and limited to the trophoblast. The pattern of VEGF and VEGF-receptor reactivity in placentas from women with overt diabetes was similar to that of normoglycemic women. In women with gestational diabetes, strong staining for VEGFR-1 was observed in vascular and trophoblastic cells whereas VEGF and VEGFR-2 were detected only in the trophoblast. The expression of these proteins was confirmed by western blotting, which revealed the presence of an additional band of 75 kDa. In the decidual compartment, only extravillous trophoblast reacted with all antibodies. Morphological analysis revealed collagen deposition around large arteries in all groups with altered glycemia. These findings indicate a placental response to altered glycemia that could have important consequences for the fetus. The change in the placental VEGF/VEGFR expression ratio in mild hyperglycemia may favor angiogenesis in placental tissue and could explain the hypercapillarization of villi seen in this gestational disturbance. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Angiogenesis; Gestational diabetes; Hyperglycemia; Overt diabetes; Trophoblast; VEGF